Edward Torikian. His Life, Activities, Influences Polyphony In Arabic Songs - Slikhanian-Kourtian, Betty (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Edouard Torikian is an artist of Armenian descent with an impressive musical career in Lebanon. A composer, musicologist, choirmaster, educator, lecturer, and author of numerous works, Torikian is blessed with an open mind and receptiveness to different cultures to which he has been exposed, while maintaining deep attachment to his Armenian origins. He actively contributes to advancing the Lebanese, Arabic and Armenian music in their secular and non-secular forms. He devotes his research to the study of Armenian sacred chant, chiefly that of the monastery of Bzommar. With his many compositions, he expands the repertoire of the Lebanese art of music. brings innovation to traditional Lebanese, Arabic, and Armenian music through harmonization and novel arrangements of more than a hundred Lebanese, Arabic, and Armenian songs, written for choir a cappella or with accompaniment. Torikian mentors music and musicology students and conducts several choirs on religious and non-religious occasions. His vocal works are interpreted around the world by choirs of international renown; his musicological treatises are taught in Lebanon as wells as in music institutions across the Arab countries, namely Syria, Jordan, and Egypt. Below is Torikian’s biography which we present succinctly, with a focus on the milestones of his musical career, the various influences which shaped his art, and the different techniques that he applied to his polyphonic arrangements of Arabic songs. Էդուարդ Թորիկյան՝ ծագումով հայ երաժիշտ, ում տպավորիչ կարիերան ծավալվել է Լիբանանում։ Կոմպոզիտոր, երաժշտագետ, խմբավար, մանկավարժ, բանախոս, բազմաթիվ գիտական աշխատությունների հեղինակ, Թորիկյանն ակտիվորեն նպաստում է լիբանանյան, արաբական և հայկական ինչպես աշխարհիկ, այնպես էլ հոգևոր երաժշտության զարգացմանը։ Բաց մտածողությամբ և իրեն շրջապատող մշակույթների նկատմամբ ընկալունակությամբ օժտված երաժիշտը խորապես կապված է իր հայկական արմատներին։ Իր գիտական աշխատանքը նա նվիրել է հայ հոգևոր երգին, մասնավորապես՝ Զմմառի վանքում կատարվող տարբերակին։ Թորիկյանի բազմաթիվ ստեղծագործությունները ընդլայնում են Լիբանանի երաժշտական արվեստի շրջանակները։ Նա ներդաշնակացում է ներմուծում լիբանանյան, արաբական և հայկական ավանդական երաժշտության մեջ, ստեղծում է երգչախմբի համար գրված a cappella կամ նվագակցությամբ կատարվող երգերի հարյուրից ավելի ինքնատիպ վերադաշնակումներ։ Թորիկյանն ուսուցանում է երաժիշտ և երաժշտագետ ուսանողներին, ղեկավարում է երգչախմբերի ելույթներ եկեղեցական և ոչ-եկեղեցական միջոցառումներում։ Նրա վոկալ երկերը հնչում են միջազգային հռչակ ունեցող երգչախմբերի կատարմամբ աշխարհի շատ երկրներում։ Երաժշտագիտությանը նվիրված նրա աշխատությունները դարձել են ուսումնական ձեռնարկներ Լիբանանի, ինչպես նաև այլ արաբական երկրների՝ Սիրիայի, Հորդանանի, Եգիպտոսի երաժշտական ուսումնական հաստատություններում։ Эдуард Торикян – музыкант армянского происхождения, впечатляющая карьера которого состоялась в Ливане. Композитор, музыковед, хормейстер, педагог, оратор, автор множества научных трудов, Торикян активно способствует развитию ливанской, арабской и армянской музыки – как светской, так и духовной. Наделенный открытым умом и восприимчивостью к составляющим его среду культурам музыкант глубоко привязан к своим армянским корням. Свой научный труд он посвятил изучению армянского духовного песнопения на примере вариантов, исполняемых в монастыре Зммар. Многочисленные произведения Торикяна расширяют границы музыкального искусства Ливана. Он привносит в традиционную ливанскую, арабскую и армянскую музыку гармони-зацию, создает оригинальные аранжировки более чем ста песен, написанных для хора a cappella или с сопровождением. Торикян обучает студентов – музыкантов и музыковедов, дирижирует хорами на церковных и внецерковных мероприятиях. Его вокальные произведения исполняются пользующимися между-народным признанием хорами во многих странах; его музыковедческие трактаты служат учебными пособиями в музыкальных образовательных учреждениях Ливана и других арабских стран – Сирии, Иордании, Египта.
Keywords: Musicology